OLVER’S METHOD FOR SOLVING ROOTS OF p-ADIC POLYNOMIAL EQUATIONS - Rabago, Julius Fergy Tiongson (Italian Journal of Pure and Applied Mathematics, 2016)
Let \(\mathbb{Z}\)p[x] be the set of all functions whose coeﬃcients are in the field of p-adic integers \(\mathbb{Z}\)p. This work considers a problem of finding a root of a polynomial equation P(x) = 0 where P(x) ∈ \(\mathbb{Z}\)p[x]. The solution is approximated through an analogue of Olver’s method for finding roots of polynomial equations P(x) = 0 in \(\mathbb{Z}\)p.